2014
DOI: 10.1093/dnares/dst057
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Diversity of DNA Structure-Related Sequence Features in Prokaryotic Genomes

Abstract: Prokaryotic genomes are diverse in terms of their nucleotide and oligonucleotide composition as well as presence of various sequence features that can affect physical properties of the DNA molecule. We present a survey of local sequence patterns which have a potential to promote non-canonical DNA conformations (i.e. different from standard B-DNA double helix) and interpret the results in terms of relationships with organisms' habitats, phylogenetic classifications, and other characteristics. Our present work d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…In silico analysis revealed that the majority of the repeat sequences found were classified as palindromic elements (1,171 elements) compared with tandem repeats (144 elements). Similar results were also reported by Huang et al [36] who investigated tandem and palindromic repeats in protein-coding sequences and intergenic regions through a global analysis of more than 1,000 genomes, including Mycoplasma agalactiae , M . bovis , M .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In silico analysis revealed that the majority of the repeat sequences found were classified as palindromic elements (1,171 elements) compared with tandem repeats (144 elements). Similar results were also reported by Huang et al [36] who investigated tandem and palindromic repeats in protein-coding sequences and intergenic regions through a global analysis of more than 1,000 genomes, including Mycoplasma agalactiae , M . bovis , M .…”
Section: Discussionsupporting
confidence: 87%
“…Prokaryote genomes are extremely diverse in terms of nucleotide composition and the presence of distinct patterns of repeat sequences that could affect the physical properties of DNA molecules [36]. In this work, a global analysis of tandem and palindromic repetitive elements found in noncoding sequences of M .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore this has been recognized as a plausible strategy for gene therapy, by removing the viral DNA and using the virus as a vehicle to deliver the therapeutic DNA. A number of viruses have been used for human gene therapy, including retrovirus, adenovirus, lentivirus, herpes simplex virus, vaccinia, pox virus, and adeno-associated virus [11,12,13].…”
Section: Introductionmentioning
confidence: 99%